2013
DOI: 10.5812/jjm.4972
|View full text |Cite
|
Sign up to set email alerts
|

Relative Frequency of Echovirus 30 in Patients Suffering from Enterovirus Meningitis in Ahvaz

Abstract: Background: Human enteroviruses are members of Picornaviridae family; they are non-enveloped, icosahedral viruses with positive RNA as genome. Echovirus 30 is an important member of enteroviruses that is recognized in outbreaks of enterovirus meningitis. Objectives: The aim of this study was to determine relative frequency of echovirus 30 as an important agent of aseptic meningitis among children referred to Aboozar hospital, Ahvaz, Iran. Patients and Methods: 34 cerebrospinal fluid samples from patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…35 ). Uncomplicated febrile seizures occurred in one child (3 years of age) in our patients group, whereas more cases have been reported by others 2,35,36 . Some patients were admitted with symptoms lasting for 14 days.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…35 ). Uncomplicated febrile seizures occurred in one child (3 years of age) in our patients group, whereas more cases have been reported by others 2,35,36 . Some patients were admitted with symptoms lasting for 14 days.…”
Section: Discussioncontrasting
confidence: 52%
“…Detection of specific antibodies (by ELISA) can be helpful in cases of diagnostic problems. Many studies have confirmed the importance of EV RNA detection by PCR in diagnosing EV meningitis in terms of faster diagnosis, avoiding unnecessary antibiotic therapy, and reducing the costs and duration of hospitalization 2,3,12,17,30,31,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study from south of Iran (Ahvaz city in Khuzestan province) enteroviruses were detected in 52.63% of CSF specimens (16). There are also other reports from Ahvaz about the frequency of enteroviruses in one of the hospitals in Ahvaz and the frequency of Echo 30 in enteroviral meningitis patients (17,18). Another study showed that the frequency of enteroviruses in viral meningitis in Tehran is similar to other countries (1,2,(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 75%